Effectiveness of Acupuncture Therapy in Combination with Rosella Tea on Changes in Blood Pressure in Hypertension Cases in Krajan, Mojosongo - Ayu, Nur Wahyu Ningtyas; Zulaika, Chusnul; Sholihah, Imrok Atus; Badri, Sholichan (HAKTI : Indonesian Acupuncture Therapists Association, 2025)
Hypertension is high blood pressure with systolic values above 140 mmHg and diastolic values above 90 mmHg. Acupuncture therapy with a combination of rosella tea steeping is a nonpharmacological treatment that has been shown to have an effect in lowering blood pressure. The purpose of this study was to determine the effect of acupuncture therapy with a combination of Rosella tea steeping on changes in blood pressure in cases of hypertension in Krajan Hamlet, Mojosongo. This study used a